2016
DOI: 10.1177/1687814016652080
|View full text |Cite
|
Sign up to set email alerts
|

Visual nesting system for irregular cutting-stock problem based on rubber band packing algorithm

Abstract: This article deals with the packing problem of irregular items allocated into a rectangular sheet to minimize the waste. Conventional solution is not visual during the packing process. It obtains a reasonable and relatively satisfactory solution between the nesting time and nesting solution. This article adopts a physical method that uses rubber band packing algorithm to simulate a rubber band wrapping those packing irregular items. The simulation shows a visual and fast packing process. The resultant rubber b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 21 publications
0
10
0
6
Order By: Relevance
“…The average time used to construct the starting points (fifth column) and the average time (sixth column) that was spent to solve the instances are also presented in the Table 2, as well as those results of the recent literature that allow free rotations. For these methods, the strip length and time reported in [31] are in seventh and eighth columns, and strip length and time reported in [16] are in ninth and tenth columns, respectively. For those instances tested in [31], it can be observed that the length in the best solution obtained in this work is slightly greater than those reported there.…”
Section: Comparing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average time used to construct the starting points (fifth column) and the average time (sixth column) that was spent to solve the instances are also presented in the Table 2, as well as those results of the recent literature that allow free rotations. For these methods, the strip length and time reported in [31] are in seventh and eighth columns, and strip length and time reported in [16] are in ninth and tenth columns, respectively. For those instances tested in [31], it can be observed that the length in the best solution obtained in this work is slightly greater than those reported there.…”
Section: Comparing Resultsmentioning
confidence: 99%
“…Additionally in the literature, we also find a visual system for packing problem of irregular pieces with free rotation into a rectangular board that aims to minimize the waste, [16]. This algorithm is based on a method of physics, the rubber band physics movement.…”
Section: Introductionmentioning
confidence: 99%
“…Resolvemos o modelo que representa o problema de empacotamento de itens irregulares em faixa apresentado neste trabalho para as instâncias da Tabela 1. Usamos 10 soluções iniciais diferentes e comparamos nossos resultados com alguns resultados da literatura que também permitem rotações livres, (STOYAN; PANKRATOV; ROMANOVA, 2016) e (LIAO et al, 2016). Esses resultados estão resumidos na Tabela 3, na qual são apresentadas o mínimo (segunda coluna), a média (terceira coluna) e o máximo (quarta coluna) dos comprimentos obtidos.…”
Section: Comparação Dos Resultadosunclassified
“…Por último, um sistema visual para o ISPP com rotação livre que visa minimizar o desperdício foi encontrado na literatura (LIAO et al, 2016). Nesse artigo é usado o algoritmo de empacotamento de elástico para resolver o problema.…”
Section: Representação Do Problema Pelo Próprio Leiauteunclassified
See 1 more Smart Citation